The use of antenatal and postnatal care: perspectives and experiences of women and health care providers in rural southern Tanzania - Mushi Adiel K; Haws Rachel A; Schellenberg Joanna; Obrist Brigit; Mrisho Mwifadhi; Mshinda Hassan; Tanner Marcel; Schellenberg David (BMC, 2009)
Abstract Background Although antenatal care coverage in Tanzania is high, worrying gaps exist in terms of its quality and ability to prevent, diagnose or treat complications. Moreover, much less is known about the utilisation of postnatal care, by which we mean the care of mother and baby that begins one hour after the delivery until six weeks after childbirth. We describe the perspectives and experiences of women and health care providers on the use of antenatal and postnatal services. Methods From March 2007 to January 2008, we conducted in-depth interviews with health care providers and village based informants in 8 villages of Lindi Rural and Tandahimba districts in southern Tanzania. Eight focus group discussions were also conducted with women who had babies younger than one year and pregnant women. The discussion guide included information about timing of antenatal and postnatal services, perceptions of the rationale and importance of antenatal and postnatal care, barriers to utilisation and suggestions for improvement. Results Women were generally positive about both antenatal and postnatal care. Among common reasons mentioned for late initiation of antenatal care was to avoid having to make several visits to the clinic. Other concerns included fear of encountering wild animals on the way to the clinic as well as lack of money. Fear of caesarean section was reported as a factor hindering intrapartum care-seeking from hospitals. Despite the perceived benefits of postnatal care for children, there was a total lack of postnatal care for the mothers. Shortages of staff, equipment and supplies were common complaints in the community. Conclusion Efforts to improve antenatal and postnatal care should focus on addressing geographical and economic access while striving to make services more culturally sensitive. Antenatal and postnatal care can offer important opportunities for linking the health system and the community by encouraging women to deliver with a skilled attendant. Addressing staff shortages through expanding training opportunities and incentives to health care providers and developing postnatal care guidelines are key steps to improve maternal and newborn health.